Case report: Unique FLT4 variants associated with differential response to anlotinib in angiosarcoma - Gu, Yuanyuan; Meng, Jing; Ju, Yongzhi; You, Xia; Sun, Tingting; Lu, Jun; Guan, Yin (Frontiers in Oncology, 2022)
Angiosarcoma (AS) is a rare, clinically aggressive tumor with limited treatment options and a poor prognosis. Mutations involving the angiogenesis-related genes PTPRB, PLCG1, KDR as well as FLT4 amplification have been observed in AS. There is a potential therapeutic value of inhibition of the VEGF pathway against angiosarcoma. Our case first described a patient with two sites of cutaneous angiosarcomas (cASs) that responded differently to anlotinib. And genetic analysis revealed that those two sites had different FLT4 variants, suggesting that FLT4 amplification could be the cause of anlotinib non-response.